Diagnostik und Behandlung physischer Frailty - Braun, Tobias; Thiel, Christian; Schulz, Ralf-Joachim; Grüneberg, Christian (DMW - Deutsche Medizinische Wochenschrift, 2017)
Physical frailty is a physiological syndrome of older people. It is characterized by a reduced reserve, a reduced stressor resistance, and vulnerability to negative health outcomes. The assessment of physical frailty is increasingly applied to identify high risk patients prior to medical or surgical interventions. The present article describes Fried’s frailty phenotype, which is the most frequently applied diagnostic instrument of physical frailty, together with evidence based treatment options.
Keywords: Gebrechlichkeit; physische Frailty; Frailty Phänotyp; geriatrisches Assessment